Women’s Empowerment and Household Decision-making: The Role of Socioeconomic Status in Indonesia - Fabian, Irvel Christa; Afrizal, Rafa Fayza (Jurnal Ekonomi Kependudukan dan Keluarga, 2025)
Understanding how women's economic, educational, and social positions influence their roles and choices within households is crucial for promoting gender equality and sustainable development. Despite significant advancements in women's rights and gender equality globally, women in Indonesia continue to face substantial barriers in achieving true empowerment. These barriers are particularly evident in domestic settings, where traditional gender roles often persist, limiting women's influence in household decisions. This research aims to investigate the relationship between women's socioeconomic status and their empowerment in domestic decision-making, examining how various factors such as income, education, and employment status contribute to or hinder their ability to influence family and household matters. This study performed a probit regression analysis using pooled cross-sectional data from the Indonesian Family Life Survey (IFLS) wave 5 (2007 and 2014) to examine the impact of women’s socioeconomic factors on the likelihood of women being empowered in domestic decision-making. Decision-making criteria included in this study concern decisions regarding spending for food consumption, daily needs and sanitation, tertiary household equipment, cash transfers to parents/relatives, and household saving. The results indicate that being employed and having higher levels of education significantly increase the probability of women having a say in household decisions. Conversely, lower socioeconomic status is strongly associated with reduced decision-making power for women. This study concludes with policy recommendations aimed at enhancing women's socioeconomic status and promoting gender-equitable decision-making within households.